Feasibility of a Community Intervention for the Prevention of Suicide and Alcohol Abuse with Yup'ik Alaska Native Youth: The Elluam Tungiinun and Yupiucimta Asvairtuumallerkaa Studies - Mohatt, Gerald V.; Fok, Carlotta Ching Ting; Henry, David; Allen, James (American Journal of Community Psychology, 2014)
Abstract The Elluam Tungiinun and Yupiucimta Asvairtuumallerkaa studies evaluated the feasibility of a community intervention to prevent suicide and alcohol abuse among rural Yup'ik Alaska Native youth in two remote communities. The intervention originated in an Indigenous model of protection, and its development used a community based participatory research process. Feasibility assessment aimed to assess the extent to which (1) the intervention could be implemented in rural Alaska Native communities, and (2) the intervention was capable of producing measurable effects. Scales maximally sensitive to change were derived from earlier measurement work, and the study contrasted implementation process and outcomes across the two communities. In one community, medium dose response effects ( d = .30–.50), with dose defined as number of intervention activities attended, were observed in the growth of intermediate protective factors and ultimate variables. In the other community, medium dose effects were observed for one intermediate protective factor variable, and small dose effects were observed in ultimate variables. Differences across communities in resources supporting intervention explain these contrasting outcomes. Results suggest implementation in these rural Alaska settings is feasible when sufficient resources are available to sustain high levels of local commitment. In such cases, measureable effects are sufficient to warrant a prevention trial.